E-BANKING SERVICES – FEATURES, CHALLENGES AND BENEFITS - IMOLA DRIGĂ; CLAUDIA ISAC (Annals of the University of Petrosani: Economics)
Today traditional banking services, based on lending and deposittaking operations, are only part of banking activities. Due to the emergence of a knowledgebased economy and society as information and communication technology advanced, banking services have undergone profound changes during the past decades. In order to improve the quality of customer service delivery and reduce transaction cost, banks have invested to a great extent in ICT and have adopted ICT networks for delivering a wide range of banking products and services. Banks all over the world have embraced innovative banking technologies and e-banking services in recent years. In this context, the paper aims to provide an overview of the electronic banking service highlighting various aspects of e-banking. Although e-banking offers many advantages both to corporate and individual clients, electronic banking is not without certain challenges and issues in terms of security and interest of customers.